Access-site complications and their management during transradial cardiac catheterization. (May 2012) - Bhat, Tariq; Teli, Sumaya; Bhat, Hilal; Akhtar, Muhammad; Meghani, Mustafain; Lafferty, James; Gala, Bhavesh
Transradial access for cardiac catheterization is now widely accepted among the invasive cardiology community as a safe and viable approach with a markedly reduced incidence of major access-related complications compared with the transfemoral approach. As this access technique is now being used more commonly for cardiac catheterization, it is of paramount importance to be aware of its complications and to understand their prevention and management. Some of the common complications of transradial access include asymptomatic radial artery occlusion, nonocclusive radial artery injury and radial artery spasm. Among these complications, radial artery spasm is still a significant challenge. Symptomatic radial arterial occlusion, pseudoaneurysm and radial artery perforation are rarely reported complications of the transradial approach. Early identification of these rare complications and their immediate management is of vital importance. Arteriovenous fistula, minor nerve damage and complex regional pain syndrome are very rare but have been reported. Recently, granulomas have been reported to be associated with the use of a particular brand of hydrophilic sheaths during the procedure. Generally, access-site complications can be minimized by avoiding multiple punctures, selection of smaller sheaths, gentle catheter manipulation, adequate anticoagulation, use of appropriate compression devices and avoiding prolonged high-pressure compression. In addition, careful observation for any ominous signs such as pain, numbness and hematoma formation during and in the immediate postprocedure period is essential in the prevention of catastrophic hand ischemia.